2021
DOI: 10.1002/1873-3468.14100
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CG methylation alters the long noncoding transcriptome landscape in multiple species

Abstract: The noncoding regions throughout the genome are in large part comprised of transposable elements (TEs), some of which are functionalized with long intergenic noncoding RNAs (lincRNAs). DNA methylation is predominantly associated with TEs, but little is known about its contribution to the transcription of lincRNAs. Here, we examine the lincRNA profiles of DNA methylation-related mutants of five species, Arabidopsis, rice, tomato, maize, and mouse, to elucidate patterns in lincRNA regulation under altered DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Similar research results indicate that lincRNAs also has methylation process, which is different from mRNAs lincRNAs had different DNA methylation profiles (Wang M. H. et al, 2018). And the researchers found that lincRNAs were obviously activated after CG DNA methylation (Zhao et al, 2021). Other studies have shown that the lincRNAs have two regulation of gene expression, cis and trans manner (Zhang et al, 2014;Quan et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar research results indicate that lincRNAs also has methylation process, which is different from mRNAs lincRNAs had different DNA methylation profiles (Wang M. H. et al, 2018). And the researchers found that lincRNAs were obviously activated after CG DNA methylation (Zhao et al, 2021). Other studies have shown that the lincRNAs have two regulation of gene expression, cis and trans manner (Zhang et al, 2014;Quan et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…Later research found that long non-coding RNAs with potential functions in gene regulation are widespread throughout the transcriptome (Iyer et al, 2015). The non-coding region of the genome is largely composed of transposable elements, some of which are functionalized with lincRNAs (Zhao et al, 2021). How lincRNA regulates the expression of susceptibility or resistance genes in tomato to play what role needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…1 B, lower part). In addition, absence of mCG in DNA methylation mutants has more impact on lincRNA transcription, compared to non-CG methylation in A. thaliana , O. sativa , and S. lycopersicum [60] . Hence, epigenetic modifiers universally determine transcription of protein coding genes, but their possibilities to affect transcription of lncRNA regions seem to be concerned.…”
Section: Survey Of Functional Lncrnas Associated With Epigenetic Modi...mentioning
confidence: 94%
“…The connection between lncRNAs and transposable elements, and between lncRNAs and DNA CG methylation [52,53] 4…”
Section: Introductionmentioning
confidence: 99%